2019
DOI: 10.3906/sag-1807-170
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic and hemodynamic changes of common carotid artery in obstructive sleep apnea hypopnea syndrome in a porcine model

Abstract: Background/aim: To prepare a porcine model of obstructive sleep apnea-hypopnea syndrome (OSAHS) and observe the pathological and hemodynamic changes in the common carotid artery. Materials and methods: Twelve male miniature pigs were randomly divided into the model and control group (n = 6). Pigs in the model group were kept in an air-flow negative pressure chamber at 0.96 ± 0.01 kPa, and the air oxygen content, temperature, and humidity were kept at normal culture conditions in both groups. After pigs in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…But meanwhile the experimental group showed activity decreased, sleep time increased, snoring intensity increased (43–51 dB), respiratory rate increased, peak value of negative respiratory pressure increased (3.5–4 kPa), and respiratory pressure waveform became irregular. The above characteristics are partly consistent with the parameter characteristics of human OSA patients ( 30 ).…”
Section: Characteristics Advantages and Limitations Of Existing Osa A...supporting
confidence: 85%
See 1 more Smart Citation
“…But meanwhile the experimental group showed activity decreased, sleep time increased, snoring intensity increased (43–51 dB), respiratory rate increased, peak value of negative respiratory pressure increased (3.5–4 kPa), and respiratory pressure waveform became irregular. The above characteristics are partly consistent with the parameter characteristics of human OSA patients ( 30 ).…”
Section: Characteristics Advantages and Limitations Of Existing Osa A...supporting
confidence: 85%
“…In healthy people, the transmural pharyngeal pressure is maintained from 0 to +10 mmHg during sleep. Upper airway obstruction in OSA patients is associated with transmural negative pressure during sleep ( 30 ). King et al found that when healthy controls were exposed to an environment of -10 cm H 2 O to sleep, polysomnography (PSG) results showed that upper respiratory tract obstruction did occur during sleep and induce OSA ( 31 ).…”
Section: Characteristics Advantages and Limitations Of Existing Osa A...mentioning
confidence: 99%